USING DIGITAL TOOLS IN TRANSLATING DETERMINERS IN ENGLISH AND FRENCH - Shalala Aliyeva (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article investigates the functioning of determiners in English and French through the lens of digital tools, corpus analysis, and grammatical theory. Determiners are treated as a crucial component of meaning construction, reflecting definiteness, specificity, and discourse structure. The study explores differences between English and French determiner systems and examines how digital resources, including machine translation and corpus tools, process these structures. Particular attention is given to zero article usage, definite and indefinite reference, and partitive constructions. The research combines theoretical insights from functional grammar with empirical observations drawn from corpus-based analysis. Examples illustrate how determiners behave across contexts and how digital tools handle them. The findings indicate that while technological tools significantly improve efficiency and consistency, they often fail to capture context-sensitive distinctions. The article concludes that accurate handling of determiners requires an integration of grammatical knowledge, discourse awareness, and digital resources.